Perceptions, 1990-1998 - Association of New York State Educators of the Emotionally Disturbed; Association of New York State Educators of the Emotionally Disturbed ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This document consists of all 20 issues of the journal "Perceptions" published from fall 1990 through summer 1998 (8 years). Issues include articles about methods, materials, approaches, and techniques for working with students with emotional and behavioral disorders. (CR)
Availability: Perceptions, Old Main Building, Rm 212, 75 S. Manheim Blvd., Suite 8, State University of New York, New Paltz, New York 12561-2442.
ERIC Note: For volumes 24 and 25, see ED 319 204 and ED 329 040, respectivelly. Volume 27 (included in this run) previously accessioned as ED 365 020. Normally published four issues per volume, but volumes 28 and 29 each had only two issues.
Practitioners.
Perceptions, v26-v32 Fall 1990-Sum 1998.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Behavior Disorders; Conferences; Elementary Secondary Education; Emotional Disturbances; Inservice Teacher Education; Integrated Services; Self Management; Teacher Competencies; Time on Task; Collected Works, Serials; Guides, Non-Classroom.; Reports, Descriptive